Soil erosion, climate change and global food security: challenges and strategies. (1st June 2014) - Rhodes, Christopher
An overview is presented of the determined degree of global land degradation (principally occurring through soil erosion), with some consideration of its possible impact on global food security. Most determinations of the extent of land degradation (e.g. GLASOD) have been made on the basis of "expert judgement" and perceptions, as opposed to direct measurements of this multifactorial phenomenon. More recently, remote sensing measurements have been made which indicate that while some regions of the Earth are "browning" others are "greening". The latter effect is thought to be due to fertilisation of the growth of biomass by increasing levels of atmospheric CO2, and indeed the total amount of global biomass was observed to increase by 3.8% during the years 1981 – 2003. Nonetheless, 24% of the Earth's surface had occasioned some degree of degradation in the same time period. It appears that while long-term trends in NDVI (normalised difference vegetation index) derivatives are only broad indicators of land degradation, taken as a proxy, the NDVI/NPP (net primary productivity) trend is able to yield a benchmark that is globally consistent and to illuminate regions in which biologically significant changes are occurring. Thus, attention may be directed to where investigation and action at the ground level is required, i.e. to potential "hot spots" of land degradation and/or erosion. The severity of land degradation through soil erosion, and an according catastrophic threat to the survival of humanity may in part have been overstated, although the rising human population will impose inexorable demands for what the soil can provide. However, the present system of industrialised agriculture would not be possible without plentiful provisions of cheap crude oil and natural gas to supply fuels, pesticides, herbicides and fertilisers. It is only on the basis of these inputs that it has been possible for the human population to rise above 7 billion. Hence, if the cheap oil and gas supply fails, global agriculture fails too, with obvious consequences. Accordingly, on grounds of stabilising the climate, preserving the environment, and ensuring the robustness of the global food supply, maintaining and building good soil, in particular improving its SOM content and hence its structure, is highly desirable. Those regions of the world that are significantly degraded are unlikely to support a massive population increase (e.g. Africa, whose population is predicted to grow from its present 1.1 billion to 4.2 billion by 2100), in which case a die-off or mass migration might be expected, if population control is not included explicitly in future plans to achieve food security.